La mediación de las agencias de publicidad y las agencias de medios - Pérez Ruiz, Miguel Ángel (Mediaciones Sociales, 2008)
Advertising and media agencies are carrying out an important task of professional mediation for advertisers and the mass media. Advertising agencies have done it since almost one and a half centuries ago. Media agencies have mediated roughly during a quarter of a century. The nature of this relationship is deeply determined by 1) the professional tasks which the advertisers ask for and 2) the goodness of the market economic situation. With a buoyant economy, advertisers have not hindered the work of the agencies. However, in periods of crisis, advertising agencies have experimented how their relationship has cooled because of the constant demands of advertisers, who have not doubted in applying the “more for less” axiom. In any case, it is essential to highlight the great change occurred in this mediating task: Both types of agencies started their work as strategic partners of advertisers, but have transformed into businesses which pro-vide services of the same nature. In terms of strategic collaboration, they have better technical qualification, but they are not as close.